2020
DOI: 10.4081/or.2020.8664
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach for fracture of distal humerus: Posterior <em>vs</em> lateral

Abstract: Humeral fractures have an incidence of 3-5% and a bimodal age distribution. They may occur in young patients after highenergy traumas or in elderly osteoporotic patients after low-energy injuries. In nondisplaced fractures or in elderly patients, humeral fractures are treated by conservative methods. Open reduction and internal fixation (ORIF) should be the treatment of choice in case of multi-fragmentary fractures associated with radial nerve palsy or not. ORIF is usually regarded as the gold standard treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…17 Moreover, not infrequently, the fracture can involve the distal third of the humerus requiring adjunctive open reduction and plating. 15 On the contrary, ORIF allows an anatomical reduction of the fracture but involves the exposure of the fracture site, the excision of part of the periosteum and the risk of iatrogenic damage of the radial nerve. Moreover, it is more bleeding and it has a hypothetical higher risk of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, not infrequently, the fracture can involve the distal third of the humerus requiring adjunctive open reduction and plating. 15 On the contrary, ORIF allows an anatomical reduction of the fracture but involves the exposure of the fracture site, the excision of part of the periosteum and the risk of iatrogenic damage of the radial nerve. Moreover, it is more bleeding and it has a hypothetical higher risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11]13 Two are the data relating to the MIPO technique (mean: 113.36 minutes; min: 95; max: 131.71). 15,16 WHICH SURGICAL TREATMENT IS PREFERABLE IN HUMERAL DIAPHYSEAL FRACTURES? A SYSTEMATIC REVIEW The average value related to nailing is 89.63 minutes (min: 50.8; max: 126), while the average time related to ORIF is 109.32 minutes (min: 64.2; max: 150.58).…”
Section: Surgical Timesmentioning
confidence: 99%
“…It still needs open reduction and internal fixation through the proximal and distal incisions. An incision, which allows a good fracture’s visualization, is always fundamental in order to ensure acceptable reduction and to allow the exploration of the radial nerve, not rarely involved in the trauma, as well as to protect it from possible iatrogenic damage [ 9 ]. Similar to MIPO technique, attention should be paid to the protection of blood supplies at the fracture site and the reduction of periosteum peeling.…”
Section: Discussionmentioning
confidence: 99%
“…In the posterior median approach, surgeons split triceps brachii and enter between the lateral head and long head to expose fracture [ 8 ]. Drawbacks to the posterior approach are lateral or prone patient positioning which may be problematic for polytraumatized patient or in case of thoracic trauma; radial nerve mobilization for plate application, theoretically increasing the risk of iatrogenic palsy [ 9 ]. Some scholars have proposed modified approaches, which lead to different reduction and fixation effects.…”
Section: Introductionmentioning
confidence: 99%
“…Among the plating techniques used for this purpose, two are extensively employed: lateral plating and posterior plating approaches. Both position and corresponding surgical approach have been applied successfully [14,15]. However, only few comparative studies about these two surgical techniques have been reported.…”
Section: Introductionmentioning
confidence: 99%